2020
DOI: 10.1111/ejn.15039
|View full text |Cite
|
Sign up to set email alerts
|

Age‐related decrements in cortical gyrification: Evidence from an accelerated longitudinal dataset

Abstract: Cortical gyrification has been found to decrease due to aging, but thus far this has only been examined in cross‐sectional samples. Interestingly, the topography of these age‐related differences in gyrification follows a distinct gradient along the cortex relative to age effects on cortical thickness, likely suggesting a different underlying neurobiological mechanism. Here I examined several aspects of gyrification in an accelerated longitudinal dataset of 280 healthy adults aged 45–92 with an interval between… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 66 publications
2
25
0
Order By: Relevance
“…Several studies have revealed that age-related decreases in GI show different topography than changes in CT and are more related to the parameter of SD ( 14 16 ). Furthermore, SD, GI, and FD have been reported to show positive associations with cognitive function ( 15 , 47 , 48 ). To our knowledge, there are no other reports on the age–sex-related patterns of changes in these parameters across the lifespan.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have revealed that age-related decreases in GI show different topography than changes in CT and are more related to the parameter of SD ( 14 16 ). Furthermore, SD, GI, and FD have been reported to show positive associations with cognitive function ( 15 , 47 , 48 ). To our knowledge, there are no other reports on the age–sex-related patterns of changes in these parameters across the lifespan.…”
Section: Discussionmentioning
confidence: 99%
“…In healthy adults, age-related thinning is observed across the majority of the cortex but is generally more robust in bilateral frontal cortices, superior temporal regions, and supramarginal gyri (13). Several studies have shown that global cortical gyrification reflected by GI decreases with age in several cross-sectional samples, and topography of these changes is different from CT (14,15). Age relates to lower gyrification mainly in the parietal, frontal, temporal, and occipital regions (16).…”
Section: Introductionmentioning
confidence: 99%
“…However there is a more prominent decrease in GI in the parietal cortex, which is a relatively more folded region. Madan (2021) extends this analysis by showing that the change in GI is driven by changes in the morphology of the sulci, becoming shallower and wider as the brain ages (see also Madan, 2019). These changes to the sulci are obvious in the slices in Figure 1, which are taken roughly through the regions with the greatest GI change in Madan's analysis.…”
mentioning
confidence: 52%
“…In understanding these changes, it is helpful to have measures that capture the changes with sufficient sensitivity that individual differences can be explored. Madan (2021) tackles this problem by looking at the gradients of gyrification across the brain. Madan uses a gyrification index (GI) that captures the smoothness of the brain at each point on its surface (Schaer et al, 2012;Zilles et al, 1988).…”
mentioning
confidence: 99%
See 1 more Smart Citation